2005
DOI: 10.1148/radiol.2352040254
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed High-Intensity Focused Ultrasound Enhances Systemic Administration of Naked DNA in Squamous Cell Carcinoma Model: Initial Experience

Abstract: Local exposure to pulsed high-intensity focused ultrasound in tumors can enhance the delivery and expression of systemically injected naked DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 40 publications
6
83
0
Order By: Relevance
“…pFUS exposures similar to those employed in the present study have been used to non-invasively and nondestructively enhance the delivery of a variety of systemically administered agents in murine solid tumors including plasmid DNA (Dittmar et al, 2005), small molecules (Poff et al, 2008), nanoparticles (Frenkel et al, 2006), and monoclonal antibodies (Khaibullina et al, 2008). More recently, in a study in the murine skeletal muscle, the same exposures were shown to enhance the delivery of both systemically and locally administered nanoparticles (Hancock et al, 2009).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…pFUS exposures similar to those employed in the present study have been used to non-invasively and nondestructively enhance the delivery of a variety of systemically administered agents in murine solid tumors including plasmid DNA (Dittmar et al, 2005), small molecules (Poff et al, 2008), nanoparticles (Frenkel et al, 2006), and monoclonal antibodies (Khaibullina et al, 2008). More recently, in a study in the murine skeletal muscle, the same exposures were shown to enhance the delivery of both systemically and locally administered nanoparticles (Hancock et al, 2009).…”
Section: Discussionmentioning
confidence: 77%
“…Although changes in peak displacements were not observed, significant increases in the time required for the tissue to return back to its initial, pre-treatment state was found in all the treated tumors. Previous studies in a variety of tumors models, including HNSCC, have shown that pFUS exposures do not cause damage to the tissue (Dittmar et al, 2005;Frenkel et al, 2006;Khaibullina et al, 2008). The increase in the relaxation time in the treated tumors, which essentially indicates a reduction in tissue elasticity, must have then occurred from a decrease in the amount of fluid in the tumors.…”
Section: Figmentioning
confidence: 92%
See 3 more Smart Citations